Axial Micromotion Locking Plate Construct Can Promote Faster and Stronger Bone Healing in an Ovine Osteotomy Model - Han, Zhihua; Wu, Jianhong; Deng, Guoying; Bi, Chun; Wang, Jiandong; Wang, Qiugen (Frontiers in Bioengineering and Biotechnology, 2021)
Abstract Fixing bone fractures with controlled axial interfragmentary micromotion improves bone healing; however, the optimal type of implant construct for this purpose is still lacking. The present study describes a novel axial micromotion locking plate (AMLP) construct that allows axial interfragmentary micromotion of 0.3 or 0.6 mm. We investigated whether the AMLP constructs enhance bone healing compared to an ordinary locking plate (LP) using an ovine osteotomy model. The stiffness of the constructs was tested under axial loading. We created a 3-mm osteotomy in the left hind leg tibia of sheep that was then stabilized with a 0.3- or 0.6-mm AMLP or LP construct (n=6/group). Bone healing was monitored weekly by X-ray radiography starting from week 3 after surgery. At week 9, the specimens were collected and evaluated by computed tomography and torsional testing. We found that the AMLPs had a lower stiffness than the LP; in particular, the stiffness of the 0.6-mm AMLP construct was 86% and 41% lower than that of the LP construct for axial loads <200 N and >200 N, respectively. In the in vivo experiments, tibial osteotomies treated with the 0.6-mm AMLP construct showed the earliest maximum callus formation (week 5) and the highest volume of bone callus (9.395±1.561 cm3 at week 9). Specimens from this group also withstood a 27% greater torque until failure than those from the LP group (P=0.0386), with 53% more energy required to induce failure (P=0.0474). These results demonstrate that AMLP constructs promote faster and stronger bone healing than an overly rigid LP construct. Moreover, better bone healing was achieved with an axial micromotion of 0.6 mm as compared to 0.3 mm.